Glutathione for food and health applications with emphasis on extraction, identification, and quantification methods: a review - Al-Temimi, Anfal Alwan (2023)
Glutathione is a naturally occurring compound that plays a crucial role in the cellular response to oxidative stress through its ability to quench free radicals, thus mitigating the risk of potential damage, including cell death. While glutathione is endogenously present in different plants and animal cells, their concentration varies considerably. The alteration in glutathione homeostasis can be used as a potential marker for human diseases. In the case of the depletion of endogenous glutathione, exogenous sources can be used to replenish the pool. To this end, both natural and synthetic glutathione can be used. However, the health benefit of glutathione from natural sources derived from fruits and vegetables is still debated. There is increasingly growing evidence of the potential health benefits of glutathione in different diseases; however, the determination and in situ quantification of endogenously produced glutathione remains a major challenge. For this reason, it has been difficult to understand the bioprocessing of exogenously delivered glutathione in vivo. The development of an in situ technique will also aid in the routine monitoring of glutathione as a biomarker for different oxidative stress-mediated diseases. Furthermore, an understanding of the in vivo bioprocessing of exogenously delivered glutathione will also aid the food industry both towards improving the longevity and profile of food products and the development of glutathione delivery products for long-term societal health benefits. In this review, we surveyed the natural plant-derived sources of glutathione, the identification and quantification of extracted glutathione from these sources, and the role of glutathione in the food industry and its effect on human health.